A Cross-National Comparison of Attributional Patterns Toward Students With and Without Learning Disabilities. (January 2018) - Woodcock, Stuart; Jiang, Han
Claims of the importance of having positive perceptions and expectations of students with learning disabilities (LD) have been repeatedly made over recent years. This article aims to raise awareness of the importance of attributional beliefs in relation to the educational outcomes of students with LD in Australia and China. Australian and Chinese trainee teachers ( N = 240) who were at the end of their training were surveyed with vignettes and Likert-scale questions to ascertain their responses to students with and without LD. Overall, the findings suggest that Chinese trainee teachers' attributional pattern is more positive than that of their Australian counterparts. Implications and recommendations for research and practice are also presented.